Health care are associated with worsening of frailty in community older adults - Jair Almeida Carneiro; Cássio de Almeida Lima; Fernanda Marques da Costa; Antônio Prates Caldeira (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To identify the factors associated with the worsening of frailty in older adults resident in the community. METHODS This is a prospective, longitudinal, and analytical study. The data collection in the baseline occurred in the participants' homes from a random sampling by conglomerates. Demographic and socioeconomic variables, morbidities, and use of health services were analyzed. Frailty was measured by the Edmonton Frail Scale. The second data collection was performed after an average period of 42 months. The adjusted prevalence ratios were obtained by multiple Poisson regression analysis with robust variance. RESULTS A total of 394 older adults participated in both phases of the study, with 21.8% of them presenting worsening of the frailty condition. The variables that remained statistically associated with the transition to a worse state of frailty were: polypharmacy, negative self-perception of health, weight loss, and hospitalization over the past 12 months. CONCLUSIONS The factors associated with worsening of frailty along the studied period among older adults in the community were those related to health care. This result must be considered by health professionals when addressing frail and vulnerable older adults.